Service level agreement renegotiation framework for trusted cloud-based system - Hani, A.F.M. (Springer Verlag, 2014)
With the widespread adoption of Cloud Computing, the need for trustworthy service providers becomes more important particularly in medical and health related areas. Service terms as one of trust factors are normally defined in the Service Level Agreement (SLA) binding both providers and customers. This paper presents a framework to perform proactive SLA renegotiation during service runtime that aims to maintain trust by customers on the cloud provider. Requirements and important basis for renegotiation such as detecting SLA violation and assessing certain service level boundaries are discussed. Preliminary experimental work shows that by using historical data, the framework is able to provide suitable recommendation on the SLO values that ensures trust is maintained. Â© Springer-Verlag Berlin Heidelberg 2014.